Clinical reliability of IgG, IgA, and IgM antibodies in detecting Epstein‐Barr virus at different stages of infection with a commercial nonrecombinant polyantigenic ELISA - Gutiérrez, J. (J Clin Lab Anal, 1999)
We studied the diagnostic reliability of a modification of the Enzygnost EBV test (Behringwerke, Germany) for the detection of IgG, IgA, and IgM antibodies (Abs) in the diagnosis of Epstein‐Barr virus (EBV) disease. One hundred and twenty‐three serum samples were studied: 14 asymptomatic subjects without EBV infection, 48 patients with primary infection, 46 subjects with past EBV infection (11 patients with other acute infections), 8 patients without EBV infection but with other viral infection, and 7 patients with probable acute clonal stimulation of B lymphocytes caused by different microorganisms. Enzygnost EBV is based on an ELISA test with a pool of viral antigens. In our series the reliability of IgM for the diagnosis of recent primary EBV infection was: sensitivity 100%, specificity 95%, positive predictive value 90.5%, and negative predictive value 100%. The IgG detection with Enzygnost was: sensitivity 98%, specificity 100%, positive predictive value 100%, and negative predictive value 91.7%. Only two subjects had positive IgA. The Enzygnost test is an efficient method for the diagnosis of EBV infection although a few IgM false positives can occur. J. Clin. Lab. Anal. 13:65–68, 1999. © 1999 Wiley‐Liss, Inc.